A LOW-TEMPERATURE HEAT-CAPACITY STUDY OF SYNTHETIC ANHYDROUS MG-CORDIERITE (MG2AL4SI5O18) - Paukov I.E.; Kovalevskaya Y.A.; Rahmoun N.-S.; Geiger C.A. (My University, 2006)
The heat capacity of synthetic anhydrous Mg-cordierite (Mg2Al4Si5O18) was measured using adiabatic calorimetry between 6 and 300 K. Mg-cordierite was synthesized from a glass of stoichiometric cordierite composition at 1250 °C for one week. The refined cell dimensions using powder X-ray diffraction give a = 17.0553(2) Å, b = 9.7167(1) Å, and c = 9.3375(1) Å with V = 1547.428(1) Å3 and a distortion index of Δ = 0.25 indicating complete Al-Si ordering. The absence of channel H2O was confirmed by powder IR spectroscopy, which did not show the presence of any bands located around 3600 cm-1. The Cp results values agree with those obtained previously by Weller and Kelley (1963) who measured the Cp of Mg-cordierite between 50 K and 298 K. The calculated entropy of Mg-cordierite at standard condition is S298.150 = 404.0±1.6J/(mol·K) using the Cp data from this study. This value is in agreement with the value presented by Weller and Kelley [407.2±3.77J /(mol·K)], but appears to be very slightly lower than estimates made from various modeling studies incorporating phase-equilibrium data on Mg-cordierite.
Keywords: CALORIMETRY; CORDIERITE; CRYSTAL SYNTHESIS; LOW-TEMPERATURE STUDY